POST-COVID OLFACTORY DISORDERS IN PATIENTS IN UZBEKISTAN: PREVALENCE AND CLINICAL CHARACTERISTICS (International Conference on Medical Science, Medicine and Public Health, 2025)
In recent years, the COVID-19 pandemic has significantly altered the clinical landscape of respiratory diseases, including manifestations involving the otorhinolaryngological system. One of the most frequent and clinically significant complications of coronavirus infection is olfactory dysfunction—anosmia and hyposmia—which often persist for months following recovery. The aim of this study was to assess the prevalence and clinical-functional characteristics of olfactory disorders in patients who recovered from COVID-19 in the Republic of Uzbekistan. This work presents an analysis of data from patients presenting with complaints of olfactory impairment or loss during the post-COVID period. The frequency of anosmia and hyposmia was evaluated depending on age, sex, severity of COVID-19, duration of olfactory recovery, and the presence of concomitant ENT diseases. Particular attention was given to potential pathophysiological mechanisms of damage to the olfactory epithelium and neural pathways, as well as the effectiveness of applied therapeutic and rehabilitation methods.